If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14m + -10 = 3(4x + -2) Reorder the terms: -10 + 14m = 3(4x + -2) Reorder the terms: -10 + 14m = 3(-2 + 4x) -10 + 14m = (-2 * 3 + 4x * 3) -10 + 14m = (-6 + 12x) Solving -10 + 14m = -6 + 12x Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 14m = -6 + 10 + 12x Combine like terms: -10 + 10 = 0 0 + 14m = -6 + 10 + 12x 14m = -6 + 10 + 12x Combine like terms: -6 + 10 = 4 14m = 4 + 12x Divide each side by '14'. m = 0.2857142857 + 0.8571428571x Simplifying m = 0.2857142857 + 0.8571428571x
| 3-2x+5=12 | | 12x+42=20x+18 | | -2x+1=4 | | 250=9g+14w | | 12b^3-2b-30b=0 | | n*2*9=49 | | 240=11g+4w | | 7x=4-3(x-1) | | 3x+11=7x+3 | | 6(y-3)=24 | | 240=4w+11g | | x+7-3x=16-5x+3 | | 1.2x=.72 | | 5x-20+3=7x | | 4=7w+6 | | 4x+6=2(x+8) | | 3x=7x-20 | | 7x-3=5-2x | | 3x-2x+1=x+6 | | 3x+11+7x+3=180 | | 12=3(x-9) | | 3x+5x+10=10x-2x+10 | | 12z^3=14z^2+48z | | 2x+18=4x+10 | | 7-4y=7 | | -9x-5y=27 | | 2*(ln(x))+1=0 | | x-4(x+3)=12 | | 8q+5=2 | | 50q-43=52q-18 | | 250=14w+9g | | 6x-1=7(x+9) |